Systematic evaluation of thin electrically insulating layers on common engineering materials - Schmaljohann, F.; Hagedorn, D.; Löffler, F. (International Conference on Plasma Surface Engineering, 2013)
Thin insulating layers are often required for typical engineering materials, e.g. steel, alumina, titanium and the respective alloys. A very dense insulating layer for subsequent conducting layers acting as electrical paths is crucial. Experiments have shown, however, that the electrical insulation of such substrates is often not sufficient or fails completely and is seldom repeatable. To determine the most important influences regarding the insulation, a systematic evaluation based on a screening design of experiments for the variation of ten parameters is introduced. The films were deposited using a radiofrequency magnetron sputter system and a non-reactive process as well as a SiO2 target for the deposition of the insulation. A thin layer of a Cu-Ni-alloy was successively deposited through a mask on top of the insulating layer. The resistance between the substrate material and the conducting layer was investigated to determine the major influencing parameters with respect to the quality of the insulation layer. Based on the results, further experiments on film thickness variations with less parameters were carried out and Al2O3 layers were compared to those utilizing SiO2.